EU Corporate Sustainability Reporting Directive Proposal : A multiple case study on the impact on large listed Finnish companies - Honka, Marsa (My University, 2022)
The European Union Commission accepted a proposition for the Corporate Sustainability Reporting Directive (CSRD) on 21 April 2021. The CSRD’s purpose is to elevate the current reporting requirements of the Non-Financial Reporting Directive (NFRD). The proposition has a few objectives for the directive. The directive will broaden the scope of reporting companies to all large and listed companies, excluding listed micro-companies. External assurance for sustainability reports will be compulsory, and the directive includes mandatory sustainability reporting standards. The central objective of this study is to study the Corporate Sustainability Reporting Directive proposal and how it will impact large listed Finnish companies. To reach this objective, three research questions are presented: How will the CSRD change the sustainability reporting of large listed Finnish companies? What risks and opportunities does the CSRD present to large listed Finnish companies? How will the CSRD drive large listed Finnish companies to a more sustainable business? The need for sustainability reporting standardization has increased. The credibility of the reports is often low because of the absence of external audits and mandatory standards. Mandatory sustainability reporting can create mechanisms to drive significant changes in companies toward a more sustainable business. Sustainability investments can be costly in the short term, but in the long term, strong sustainability engagement can create a competitive advantage. On the other hand, large companies usually already have a high level of maturity in sustainability reporting, resulting in mandatory reporting having a less significant effect on them than smaller companies. This research is conducted as a qualitative multiple-case study. The primary data consists of six semi-structured expert interviews from six case companies. The selected interviewees are sustainability professionals from large, listed Finnish companies and auditing and consulting companies. The data is analyzed by coding using NVivo. The CSRD will increase the amount of sustainability disclosure from large listed Finnish companies, but less than compared to smaller companies. The CSRD will enhance the comparability and credibility of sustainability reports of large listed Finnish companies because of the mandatory standards and assurance. The biggest challenges for these companies regarding the CSRD relate to data measurement and reasonable assurance because qualitative sustainability data is challenging to transform into a quantitative form and reasonable assurance requires all reporting processes to be in place. However, those large listed Finnish companies that comply with the CSRD effectively can create a competitive advantage and benefit financially. The CSRD enhances sustainability reporting processes. The findings from this study show that the CSRD influences sustainability activities by increasing discussions and awareness of sustainability topics in finance teams.

EU Komissio hyväksyi Corporate Sustainability Reporting Directive (CSRD) ehdotuksen 21.4.2021. CSRD:n tarkoituksena on parannella nykyistä Non-Financial Reporting direktiiviä (NFRD). Ehdotuksella on muutama tavoite direktiiville. CSRD laajentaa raportoivien yritysten joukkoa koskemaan kaikkia suuria ja listattuja yrityksiä, lukuun ottamatta listattuja mikroyrityksiä. Ulkoinen varmennus tulee pakolliseksi osaksi raportointia ja direktiivi sisältää pakolliset EU vastuullisuusraportointi standardit (ESRS). Tämän tutkimuksen keskeinen tavoite on tutkia CSRD ehdotusta ja sen vaikutusta suuriin suomalaisiin pörssiyhtiöihin. Tämän tavoitteen saavuttamiseksi esitetään kolme tutkimuskysymystä: Miten CSRD muuttaa suurten suomalaisten pörssiyhtiöiden vastuullisuusraportointia? Mitä riskejä ja mahdollisuuksia CSRD asettaa suurille suomalaisille pörssiyhtiöille? Miten CSRD ajaa suuria suomalaisia pörssiyhtiöitä kohti kestävämpää yritystoimintaa? Vastuullisuusraportoinnin standardisoimisen tarve on kasvussa. Vastuullisuusraporttien uskottavuus on usein alhainen johtuen ulkoisen tarkastuksen sekä pakollisten raportointistandardien puutteesta. Pakollinen vastuullisuusraportointi voi luoda mekanismeja, joilla on merkittävä vaikutus yritysten kestävän kehityksen aktiviteetteihin. Lyhyellä aikavälillä, vastuullisuuteen liittyvät investoinnit voivat olla kalliita, mutta pitkällä välillä vahva sitoutuminen vastuullisuustavoitteisiin voi luoda kilpailuetua. Suurilla yrityksillä on toisaalta yleensä jo valmiiksi vahva sitoutuminen vastuullisuusraportointiin, joka johtaa siihen, että pakollisen vastuullisuusraportoinnin omaksumisella ei ole niihin niin suurta vaikutusta kuin pienemmille yrityksille. Tämä tutkimus on kvalitatiivinen monitapaustutkimus. Tutkimuksen primaarinen data muodostuu kuudesta puolistrukturoidusta asiantuntija haastattelusta kuudesta eri case-yrityksestä. Valitut asiantuntijat haastatteluihin ovat vastuullisuusasiantuntijoita sekä suurista suomalaisista pörssiyhtiöistä että tilintarkastus- ja konsultointiyrityksistä. Data analysoidaan koodaamalla NVivo-ohjelmistolla. CSRD lisää suurten suomalaisten pörssiyrityksien raportoidun vastuullisuusinformaation määrää, mutta vaikutus on vähäisempi verrattaessa pienempiin yrityksiin. CSRD parantaa suurten suomalaisten pörssiyhtiöiden vastuullisuusraporttien vertailtavuutta ja uskottavuutta pakollisten standardien ja ulkoisen varmennuksen kautta. Merkittävimpiä haasteita direktiiviin liittyen näille yrityksille on vaadittavan datan mittaaminen ja vaatimus kohtuullisesta varmennuksesta, koska kvalitatiivinen data on haastava muuttaa kvantitatiiviseen muotoon ja kohtuullinen varmennus vaatii raportointiprosessien laittamista kuntoon. Ne suomalaiset pörssiyhtiöt, jotka kuitenkin suoriutuvat hyvin CSRD vaatimuksista voivat luoda kilpailuetua ja täten saada siitä taloudellista hyötyä. CSRD tulee tehostamaan vastuullisuusraportointi prosesseja. Tämän tutkimuksen tulokset osoittavat, että CSRD:llä on vaikutusta kestävän kehityksen aktiviteetteihin lisäämällä vastuullisuusteemoista keskusteluja ja tietämystä taloustiimien keskuudessa.
Keywords: sustainability reporting, CSRD, CSR, ESG, corporate sustainability, vastuullisuusraportointi, CSRD, ESG, CSR, yritysvastuullisuus